1972
DOI: 10.3406/bulmi.1972.6688
|View full text |Cite
|
Sign up to set email alerts
|

Une typologie originale du zircon accessoire

Abstract: Les auteurs présentent une méthode d'étude statistique nouvelle des populations de zircon accessoire des roches endogènes ; cette méthode est basée sur la typologie des cristaux automorphes et subautomorphes. Les auteurs considèrent 194 types et sous˗types, observés ou théoriques, en fonction de la combinaison et du développement relatif des faces prismatiques et pyramidales. Une grille permet une représentation simple et précise des résultats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 0 publications
1
11
0
3
Order By: Relevance
“…The oldest analysed zircon reveals almost concordant age at 2,081 ± 18 Ma (1r). This is a slightly rounded, normal-prismatic, colourless, transparent zircon which can be defined as S12 subtype in classification Pupin and Turco (1972 Well Marcinki IG-1…”
Section: Detrital Zircon Geochronologymentioning
confidence: 99%
“…The oldest analysed zircon reveals almost concordant age at 2,081 ± 18 Ma (1r). This is a slightly rounded, normal-prismatic, colourless, transparent zircon which can be defined as S12 subtype in classification Pupin and Turco (1972 Well Marcinki IG-1…”
Section: Detrital Zircon Geochronologymentioning
confidence: 99%
“…Development of {211} faces is a widespread feature of zircon grains containing inheritance, but several factors may determine that morphology. Pupin and Turco (1972) attributed differential development of zircon prism faces to differences in crystallisation temperature. Pupin (1980) later suggested that the development of zircon pyramids is determined by the alkalinity of the magma, {211} pyramids becoming larger and {011} pyramids smaller as magmas become less alkaline and more aluminous.…”
Section: Metamorphic Zircon Growthmentioning
confidence: 99%
“…The typomorphic implications of zircon crystal morphology are determined by the relationship between the faceting of individual grains and their crystallization conditions (Pupin and Turco, 1972;Brodskaya et al, 1986). The morphological parame ters of the zircons studied and plotted on Pupin's dia gram (Fig.…”
Section: Geochronology Isotope Geochemistry and Crystal Morphology mentioning
confidence: 99%